IP network configuration for intradomain traffic engineering. - Feldmann, A. (IEEE Network : the magazine of global information exchange)
The smooth operation of the Internet depends on the careful configuration of routers in thousands of autonomous systems throughout the world. Configuring routers is extremely complicated because of the diversity of network equipment, the large number of configuration options, and the interaction of configuration parameters across multiple routers. Network operators have limited tools to aid in configuring large backbone networks. Manual configuration of individual routers can introduce errors and inconsistencies with unforeseen consequences for the operational network. In this article we describe how to identify configuration mistakes by parsing and analyzing configuration data extracted from the various routers. We first present an overview of IP networking from the viewpoint of an Internet service provider and describe the kinds of errors that can appear within and across router configuration files. To narrow the scope of the problem, we then focus our attention on the configuration commands that relate to traffic engineering-tuning the intradomain routing protocol to control the flow of traffic through the ISP network. We present a case study of a prototype tool, developed in collaboration with AT&T IP Services, for checking the configuration of the AT&T IP Backbone and providing input to other systems visualization and traffic engineering